EVALUATION OF ORAL MUCOSAL MICROBIOTA IN CHILDREN AND ADOLESCENTS AFFECTED BY CHRONIC GINGIVITIS (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
The pathogenic potential of certain representatives of the oral microbiota is quite pronounced and may be realized under various conditions, both from the transient flora and from the resident microbiota [1-3]. Researchers believe that the identified qualitative and quantitative shifts in the oral auto-microflora in children with chronic catarrhal gingivitis may lead to prolonged disease course, frequent relapses, and chronic progression [4-6].